Exploring molecular biomarkers with potential prognostic value in longitudinal observational studies on Alzheimer's disease: Developing topics. (7th December 2020) - Vanmechelen, Eugeen; Goossens, Julie; Dewit, Nele; Smirnov, Denis S; Jacobs, Dirk; Belbin, Olivia; Alcolea, Daniel; Lleó, Alberto; Galasko, Doug R
Abstract: Background: Incorporation of biomarkers into the diagnosis of AD has shifted its disease definition from clinical dementia (on average 7 years) into a biological change that may span two decades of a human life. Synaptic biomarkers and neurofilament light (NfL) have shown some potential to predict stage and disease course, however few studies have combined these markers in larger sample sets. Method: Negative controls, preclinical subjects (n=90), and subjects with MCI (n=57) and mild AD (n=46) from the longitudinal observational study at the UCSD Shirley‐Marcos ADRC (UCSD cohort) were tested for their biomarker levels. One molecular/synaptic marker, neuronal pentraxin 2 (NPTX2), is quantified in CSF with an ELISA containing two monoclonal antibodies (mAbs). We describe a newly developed NfL assay based on two mAbs that specifically targets the C‐terminus of coil 2a from human NfL. A third marker is synaptobrevin 2 (VAMP2), an essential component of the synaptic vesicle. Classical biomarkers such as t‐tau, β‐amyloid42 and synaptic markers SNAP25 and neurogranin were available for this sample set. Result: As expected, CSF NfL levels increase gradually over the course of the disease, while VAMP2, as well as SNAP25 and neurogranin, shows a significant change in a stage of AD characterized by low Aβ42 and normal CSF tau and CSF NfL levels, thus suggesting that synaptic changes may precede overt neuronal (axonal) damage. CSF NPTX2 is a robust biochemical reflection of cognitive decline, as defined by California Verbal Learning Tests and Mattis Dementia Rating Scale and in contrast to all other fluid markers, it is not age‐dependent in control individuals. Conclusion: Exploring all these biochemical markers in observational longitudinal studies suggests changes might delineate different stages in the disease process: (1) intracellular synaptic markers such as VAMP2, SNAP25 and neurogranin precede neuronal degeneration as defined by increased CSF tau and CSF NfL levels, while NPTX2 only begins to decrease towards late clinical stages, showing a robust correlation to cognitive decline. When further verified and/or validated in other well‐designed longitudinal studies, such prognostic biomarkers might define specific stages and predict the onset of specific pathophysiological progression during the long course of the disease.